PERAN DUTA GENRE (GENERASI BERENCANA) DALAM MENUMBUHKAN KESADARAN SOSIAL GENERASI-Z PADA KASUS PERKAWINAN USIA ANAK DI KECAMATAN POGGOK KABUPATEN BLITAR - Sari, Vemy Indah; Jatiningsih, Oksiana (Kajian Moral dan Kewarganegaraan, 2024)
Abstract The role of teenagers in changing character and morals in social life has a top priority. The research, which was motivated by the lack of social awareness in Generation Z, regarding the promiscuity of teenagers, caused cases of child marriage to soar. Marriage dispensation is not the only way to resolve teenage problems caused by pregnancy out of wedlock. The cultivation of social awareness also includes the role of parents by providing youth education counseling by the Blitar Regency Planning Generation Ambassador. Through interviews involving Blitar Regency GenRe Ambassadors and conducting participant observation through method outreach activities in research carried out by means of interviews, observation and documentation. In the research conducted, it was found that the role of GenRe Ambassadors as an extension of the Blitar Regency Women's Empowerment, Child Protection, Population Control and Family Planning Service was an important factor in approaching peers through outreach. implemented in a re-educational normative approach which will later reduce five core issues from the standard theory of Biddle and Thomas's role in the peer group. The results of research findings in research related to the role of GenRe Ambassadors in fostering social awareness in generation z in Ponggok District, Blitar Regency can be mapped into several things. that exist, namely: 1) Conducting counseling with a normative re-educative approach to teenagers 2) Guiding parents regarding supervision of teenagers 3) Youth campaign through social media as a preventive effort to raise social awareness for teenagers 4) Skeptical attitudes towards generation z as GenRe Ambassadors carry out counseling on marriage dispensations. 5) Lack of active GenRe Ambassador members in village areas. Keywords: Planning Generation Ambassador, Role, Social Awareness